Synoptic tables of sexually transmitted diseases: a practical approach to syphilis - Hickmann, Helen Luize; Zampese, Márcia; Ramos, Mauro Cunha (Brazilian Journal of Sexually Transmitted Diseases, 2020)
In our dermatological practice, we, as many colleagues who are dedicated to similar specialties, see more and more patients with syphilis. This increase can also be observed in international as well as national publications, especially in the Epidemiological Bulletin of Syphilis published regularly by the Brazilian Ministry of Health. Public and, to a lesser extent, private health institutions have been trying to control the current epidemic. Universities and National Health Professional Councils have also addressed the issue. Medical associations, especially the Brazilian Society of Sexually Transmitted Diseases, have an important role in educational initiatives to disseminate knowledge and good practices for the prevention and care of people with syphilis. [...]